2016
DOI: 10.1016/j.cels.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of Generalizable RNA-Protein Hybrid Controllers by Level-Matched Genetic Signal Amplification

Abstract: Summary For synthetic biology applications, protein-based transcriptional genetic controllers are limited in terms of orthogonality, modularity, and portability. Although ribozyme-based switches can address these issues, their current two-stage architectures and limited dynamic range hinder their broader incorporation into systems-level genetic controllers. Here, we address these challenges by implementing an RNA-protein hybrid controller with a three-stage architecture that introduces a transcription-based am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…In addition we showed that combining STARs with inducible promoter systems could tune their transfer functions, which to date has been largely achieved through engineering of DNA promoters and protein transcription factors 53 . Thus STARs add to an increasingly powerful toolbox of regulators that can be used in composite with existing regulatory mechanisms to alter their regulatory properties 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition we showed that combining STARs with inducible promoter systems could tune their transfer functions, which to date has been largely achieved through engineering of DNA promoters and protein transcription factors 53 . Thus STARs add to an increasingly powerful toolbox of regulators that can be used in composite with existing regulatory mechanisms to alter their regulatory properties 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, synthetic biologists have engineered a diverse array of RNA regulators that can be used to control many of the core processes of gene expression including transcription [2][3][4][5] , translation [6][7][8] and mRNA degradation [9][10][11][12] . In addition to being able to tune the expression of individual genes, these engineered RNA regulators have also been connected together to create synthetic gene networks in the form of logic gates 2,3,5,7,13 , cascades 2,5,[13][14][15][16][17] , single input modules 5,16 feed forward loops 18 , and hybrid feedback controllers 12 . While these synthetic network motifs showcase some of the advantages of RNA regulators, they represent the beginning of larger efforts to create a greater diversity of RNA network function that is necessary to engineer higher order cellular behavior.…”
Section: Introductionmentioning
confidence: 99%
“…RNA biosensors have been used as genetically-encoded controllers for a variety of synthetic biology applications 41,42 . Expanding the diversity of ligand-responsive RNA switches can increase the number and complexity of logical operations in biological circuits [43][44][45] . In biomanufacturing, biosensors that can monitor the accumulation of intermediate or product metabolites can be applied to generate screens of selections for improved enzyme activity or pathway flux 15,46 or to implement dynamic feedback control 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Expanding the diversity of ligand-responsive RNA switches can increase the number and complexity of logical operations in biological circuits [43][44][45] . In biomanufacturing, biosensors that can monitor the accumulation of intermediate or product metabolites can be applied to generate screens of selections for improved enzyme activity or pathway flux 15,46 or to implement dynamic feedback control 45 . Biosensors that responds to small molecule drugs with safe pharmacological profiles (e.g., aciclovir, gardiquimod) can enable the generation of conditional genetic controllers for CRISPR/Cas9-based therapies 29 , gene therapies 47 , and cell therapies 48,49 , to mitigate toxic effects of prolonged transgene expression or cell activation 12 .…”
Section: Discussionmentioning
confidence: 99%